2021
DOI: 10.1371/journal.pmed.1003801
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of young onset dementia and associations with comorbidities: A study of data from the French national health data system

Abstract: Background Dementia onset in those aged <65 years (young onset dementia, YOD) has dramatic individual and societal consequences. In the context of population aging, data on YOD are of major importance to anticipate needs for planning and allocation of health and social resources. Few studies have provided precise frequency estimates of YOD. The aim of this study is to provide YOD prevalence and incidence estimates in France and to study the contribution of comorbidities to YOD incidence. Methods and findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Of these, 61 articles reported on the incidence of YOD and were included in this systematic review (eFigure A). 9,10,18–76 …”
Section: Resultsmentioning
confidence: 99%
“…Of these, 61 articles reported on the incidence of YOD and were included in this systematic review (eFigure A). 9,10,18–76 …”
Section: Resultsmentioning
confidence: 99%
“…The higher prevalence of CNS-active medication polypharmacy among patients with EOD (vs with LOD) is likely because the former group had a higher prevalence of seizures [ 6 ] and neuropsychiatric symptoms [ 7 ], leading to increased use of anticonvulsants and antidepressants, two commonly prescribed therapeutic classes of CNS-active medications observed in the study sample with EOD. Also, patients with EOD tended to have substance abuse and traumatic brain injury [ 8 ], risk factors associated with the use of multiple CNS-active medications observed in the present and previous studies [ 30 ]. The present study also observed a high percentage (43.5%) of patients with EOD who had a comorbid chronic pain diagnosis, a condition that strongly predicts the use of multiple CNS-active medications [ 18 ].…”
Section: Discussionmentioning
confidence: 83%
“…Compared with patients with LOD, those with EOD were more likely to develop seizures [ 6 ] and neuropsychiatric symptoms, such as depression (41% vs 26%), and anxiety (28% vs 14%) [ 7 ]. Also, patients with EOD have a high prevalence of substance abuse disorder (e.g., alcohol dependence; 14.6%) and traumatic brain injury (6.4%) [ 8 ], strong predictors of persistent opioid use [ 9 , 10 ]. Those conditions may predispose patients with EOD to the risk of using multiple CNS-active medications, or CNS medication polypharmacy.…”
Section: Introductionmentioning
confidence: 99%
“…The 2 groups were frequency matched in a 1:1 ratio by age (within a 5-year span), sex, and index year, as implemented in other studies, 33 , 34 because these characteristics have been recognized as confounders for associations between traffic injuries and dementia. 18 , 21 , 35 For the group without dementia, the index date was January 1 of each year between 2006 and 2012.…”
Section: Methodsmentioning
confidence: 99%
“…For the group without dementia (reference group), we randomly selected individuals with no dementia diagnosis throughout the study period; the exclusion criteria for this cohort were the same as those used for the group with dementia. The 2 groups were frequency matched in a 1:1 ratio by age (within a 5-year span), sex, and index year, as implemented in other studies, because these characteristics have been recognized as confounders for associations between traffic injuries and dementia . For the group without dementia, the index date was January 1 of each year between 2006 and 2012.…”
Section: Methodsmentioning
confidence: 99%